Hubungan Tingkat Kemandirian Melakukan Activity of Daily Living (ADL) dengan Kualitas Hidup Lansia di Rumah Pelayanan Sosial Semarang - Asyirofi Borrys Rajj; Moch Aspihan; Iskim Lutfha (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Age-related decline often affects the elderly’s ability to perform Activities of Daily Living (ADL). Reduced functional capacity may lead to greater dependence and negatively influence physical and psychological well-being. The quality of life of older adults is closely linked to their ability to remain independent in daily activities. Understanding this relationship is essential to improving elderly care services. This study aimed to examine the association between ADL independence and quality of life among elderly residents in Pucang Gading Semarang and Wening Wardoyo Ungaran Social Care Homes. A quantitative design with a cross-sectional approach was employed. The Barthel Index was used to assess ADL independence, while the WHOQOL-OLD questionnaire measured quality of life. A total of 135 elderly individuals were selected through purposive sampling based on predetermined inclusion criteria. The association between variables was analyzed using Somers’ d to determine significance and direction of the relationship. Most participants demonstrated independent ADL performance, and the majority reported high quality of life. Statistical analysis showed a p-value of 0.000 and an r-value of 0.581, indicating a significant and positive relationship between ADL independence and quality of life. This study confirms that independence in performing daily activities is significantly associated with better quality of life among elderly residents. Greater ADL independence contributes to improved well-being within the social care environment.